Implementation of Innovation Strategy for Business Growth: A Case Study at Selfscape Studio - Nuzul Rachmatiyah; Isti Raafaldini Mirzanti (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2025)
The decline in revenue experienced by Selfscape Studio highlights the need to redefine the business strategy to remain competitive and respond to changing customer preferences. As an independent photo studio offering personal photography services, Selfscape faces challenges from increasing competition and shifting market trends. This study aims to formulate a strategic framework for Selfscape Studio to address these challenges through growth strategies identified using the Ansoff Matrix.This study uses a structured conceptual framework that includes internal analysis, such as Resources-Based View (RBV), VRIO, and Value Chain Analysis, as well as external analysis, such as PESTLE, Porter’s 5 Forces, Competitor Analysis, and Customer Insight. The findings from this analysis are formulated into SWOT and TOWS matrices to identify relevant strategies. A mixed-method approach was used, combining qualitative and quantitative methods. Data were collected through desk studies, observations, focus group discussions (FGDs) with stakeholders, and a survey of 200 loyal customers who have made at least two transactions.The results show that Product Development is the most relevant growth strategy for Selfscape Studio, as identified through the Ansoff Matrix. The proposed innovation strategy includes the introduction of AI-based editing services, personalized thematic photo packages, and a self-service product photo booth for MSMEs. This strategy is designed to enhance customer experience, expand market reach, and strengthen the company’s unique value proposition.